Determinants of Hypertension Incidence Among Adult Men in the Working Area of Limboto Health Center, Gorontalo Regency - Yeni Paramata; Safrudin Tolinggi; Rahmawati Rahmawati; Marselia Sandalayuk; Nabila H. Gani (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Hypertension is estimated to affect 1 13 billion people in the world. The purpose of this study was to analyze the determinants of hypertension in adult men in the Limboto Health Center working area. This type of analytic observational research uses a cross-sectional study design. The population is the entire population of adult males aged 25-45 years. Sampling was conducted using purposive sampling with a total of 108 participants. Research data were obtained through questionnaires, measuring blood pressure, measuring height, weight, and abdominal circumference. Univariate analysis showed that 48 1% of respondents had hypertension. The results of the chi-square test showed that age (p value 0,037<0,05), central obesity (p value 0,010<0,05) and physical activity (p value 0,015<0,05) had a relationship with the incidence of hypertension. However, smoking behavior (p value 0,204>0,05), alcohol consumption behavior (p value 0,189>0,05), and sodium consumption patterns (p value 0,062>0,05) have no relationship with the incidence of hypertension. The variables of age, central obesity, and physical activity are factors associated with the incidence of hypertension in the working area of the Limboto Community Health Center, Gorontalo Regency.